معجزات موسى  بين القرآن والتوراة-دراسة مقارنة- - قاسمي, خديجة; بن عبد الحميد, نوال (جامعة الوادي university of eloued, 2019)
كانت هذه المذكرة حول دراسة معجزات موسى  بين التوراة والقرآن الكريم، ولقد قمنا بدراسة تحليلية مقارنة بشكل موجز، وقد بدأنا بشرح مصطلحات العنوان أولا، ثم تطرقنا إلى ذكر المعجزات المتفق عليها بين التوراة والقرآن وهي خمسة معجزات تتمثل في معجزة العصا، ومعجزة اليد، ومعجزة الدم، ومعجزة الضفادع، وأيضا معجزة الجراد، ثم توقفنا عند إيراد المعجزات المختلف فيها في التوراة والق ران الكريم. Summary This was a memorandum on the study of the miracles of Moses peace be upon him between the Torah and the Koran and we have conducted a comparative analytical study in a brief and we began to explain the terms of the title first, and then touched on the mention of the miracles agreed between the Torah and the Koran are five miracles are the miracle of the stick, miracle hand, the miracle of blood, And the miracle of frogs, and also the miracle of the locusts. Then we stopped when we reached the different in the Torah's mracles and the Koran's miracles.
لبسانس